2023
DOI: 10.1155/2023/6128517
|View full text |Cite
|
Sign up to set email alerts
|

Mathematical-Based CFD Modelling and Simulation of Mushroom Drying in Tray Dryer

Talbachew Tadesse Nadew,
Petros Demissie Tegenaw,
Tsegaye Sissay Tedila

Abstract: In this study, CFD simulations that incorporate the inherent coupling between the moisture content of the mushroom and hot air flow in the tray dryer were performed. Conservation principles were applied to the fundamental quantities of mass, momentum, and heat. The source terms due to the moisture evaporation, the viscous and inertial resistance, and continuous evaporative cooling were determined through experimental results. Experiments were conducted to study and select the drying kinetics model at the optim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 46 publications
0
1
0
Order By: Relevance
“…Different authors have shown that Midilli et al is the best-fit drying model for mushroom drying [ 26 , 27 , 43 ]. So, Midilli et al is the model selected for studying oyster mushroom drying rate.…”
Section: Resultsmentioning
confidence: 99%
“…Different authors have shown that Midilli et al is the best-fit drying model for mushroom drying [ 26 , 27 , 43 ]. So, Midilli et al is the model selected for studying oyster mushroom drying rate.…”
Section: Resultsmentioning
confidence: 99%